Telecurso 2o grau: as apropriações televisivas do currículo para formação do estudante cliente (1978 e 1985). - Silva, Wagner Pereira [UNIFESP] (2019)
The analysis presented in this Master’s dissertation aims on the tele-education program of the Roberto Marinho Foundation and broadcast on Globo TV called Telecurso, focusing on its first phase that was concerned with the high school students, exhibited in 1978, and its reformulation, Novo Telecurso 2o Grau, exhibited in 1985. The research aims to identify how the curriculum was appropriate for a television program; as well as understand the development of this new viewer profile, the client student. It seeks to investigate the conjuncture that allowed the Telecurso project to arise and the profile of professionals involved in the project. The disciplines were also analyzed with the objective of identifying the television formats and the disciplinary characteristics present in the tele-lectures, with a in-depth examination of the Portuguese Language discipline. In this way, it is possible to find out how a distance education project was proposed by a communication vehicle and how the development of a television school culture took place.